Behavioral Neurobiology of Schizophrenia and Its Treatment - Swerdlow, Neal R. (Current Topics in Behavioral Neurosciences, 2010)
Schizophrenia research is in a dynamic state; this text gives a foothold for where we stand today, and a map for where our field may move tomorrow. Chapters on treatment describe major changes in clinical and neural targets, and new technologies for drug delivery, even as we struggle to address adverse effects of old treatments. The text next reviews advances in the experimental analysis of the schizophrenias. Where we once faced a paucity of biological signals, our field now sees an expanding list of clear neural abnormalities, and chapters focus on those in circuitry connecting prefrontal cortex, thalamus and mesial temporal lobes. The rapid evolution of schizophrenia genetics is described: older strategies for finding disorder genes, jettisoned in favor of studies of aberrant copy number variants, rare mutations or DNA methylation, and of molecular signaling pathways that trigger downstream disturbances in critical brain circuits. With what we now know about the complex biology of the schizophrenias, a key question becomes whether we can manipulate this biology in a way that fundamentally changes the course of this disorder. This text provides a context for students, investigators and clinicians to understand this stage in our evolving field, and to look ahead to the future of schizophrenia research.